Cardiac Rehabilitation Improves Endothelial Function in Coronary Artery Disease Patients - Manresa-Rocamora, Agustín; Ribeiro, Fernando; Casanova-Lizón, Antonio; Flatt, Andrew A.; Sarabia, José Manuel; Moya-Ramón, Manuel (International Journal of Sports Medicine, 2022)
Exercise-based cardiac rehabilitation may be an effective non-pharmacological intervention for improving endothelial function in coronary artery disease patients. Therefore, this systematic review with meta-analysis aimed to (a) estimate the training-induced effect on endothelial and vascular smooth muscle function, assessed by flow-mediated dilation and nitroglycerin-mediated dilation, respectively, in coronary artery disease patients; and to (b) study the influence of potential trial-level variables (i. e. study and intervention characteristics) on the training-induced effect on endothelial and vascular smooth muscle function. Electronic searches were performed in Pubmed, Scopus, and Embase up to February 2021. Random-effects models of standardised mean change were estimated. Heterogeneity analyses were performed by using the Chi2 test and I2 index. Our results showed that exercise-based cardiac rehabilitation significantly enhanced flow-mediated dilation (1.04 [95% confidence interval=0.76 to 1.31]) but did not significantly change nitroglycerin-mediated dilation (0.05 [95% confidence interval=–0.03 to 0.13]). Heterogeneity testing reached statistical significance (p<.001) with high inconsistency for flow-mediated dilation (I2=92%). Nevertheless, none of the analysed variables influenced the training-induced effect on flow-mediated dilation. Exercise-based cardiac rehabilitation seems to be an effective therapeutic strategy for improving endothelial-dependent dilation in coronary artery disease patients, which may aid in the prevention of cardiovascular events.
Keywords: flow-mediated dilation; nitroglycerin-mediated dilation; endothelium-dependent dilation; exercise-based cardiac rehabilitation; systematic review; meta-analysis